Peran Vicarious Liability Dalam Pertanggungjawaban Korporasi (Studi Terhadap Kejahatan Korupsi Yang Dilakukan Oleh Kader Partai Politik) - Muhammad Isra Mahmud (Lex Renaissance, 2020)
This study aims to identify and analyze: first, the position of political parties as private law subjects; second, the role of vicarious liability in the effort to convict legal entities of political parties. The research method used is normative juridical with a statutory approach. This study concludes that first, political parties as legal entities which are also legal subjects can be held accountable for acts of human rights violations, based on the theories and formulations of the laws and regulations that have been regulated in the Republic of Indonesia. Second, vicarious liability plays a role in efforts to punish legal entities such as political parties in the form of fines or additional penalties, which in practice experience difficulties or weaknesses.